Dynamic Governance in the Thinking Ahead Dimension: Perspectives on the Implementation of the South Sumatra Mandiri Food Movement Program - Anthony, Steven; Iriani , Atrika; Nofrima , Sanny (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
Plant, fish, and poultry farming are all part of the Food Self-Summary Movement's efforts to shift the community's perspective from "buyers" to "producers". However, there are still many challenges in its implementation, including beneficiaries still concentrating on their primary sources of income, GSMP socialization not being optimal for beneficiaries, field assistance related to plant and fish cultivation not being optimal, and assistance provided services not being fully adapted to field conditions and beneficiary skills. Therefore, it is crucial to carry out research that attempts to examine how the South Sumatra Independent Food Movement Program (GSMP) is being implemented from a Dynamic Governance perspective. So, it is expected to be able to recommend solutions for implementing the South Sumatra Independent Food Movement Program (GSMP), especially in Palembang City. The focus of this research is Dynamic Governance in the implementation of the South Sumatra Independent Food Movement Program (GSMP), which is analyzed dynamic capabilities namely: Thinking Ahead (thinking ahead). The analysis techniques used include: Data Condensation, Data Display, and Conclusion Drawing/Verifications. Data processing will use the help of the Nvivo 12 Plus application by coding the results of the interviews. This study focuses on using Thinking Ahead in dynamic governance.